Regioselective C(sp2)-C(sp3) Coupling Mediated by Classical and Rollover Cyclometalation - Lorenzo Manca; Giacomo Senzacqua; Sergio Stoccoro; Antonio Zucca (Molecules, 2024)
By taking advantage of a sequence of oxidative addition/reductive elimination reactions, Pt(II) cyclometalated derivatives are able to promote a rare C(sp2)-C(sp3) bond coupling, resulting in the production of novel methyl-substituted pyridines and bipyridines. Starting from 6-phenyl-2,2′-bipyridine, the step-by-step full sequence of reactions has been followed, leading to the unprecedented 3-methyl-6-phenyl-2,2′-bipyridine, which was isolated and fully characterized. The synthesis involves the following steps: (1) rollover cyclometalation to give the starting complex [Pt(N^C)(DMSO)Me]; (2) the synthesis of a more electron-rich complex [Pt(N^C)(PPh3)Me] by the substitution of DMSO with triphenylphosphine; (3) oxidative addition with methyl iodide to give the Pt(IV) complex [Pt(N^C)(PPh3)(Me)2(I)]; (4) iodide abstraction with silver tetrafluoborate to give an unstable pentacoordinate intermediate, which rapidly evolves through a carbon–carbon reductive coupling, forming a new C(sp3)-C(sp2) bond; (5) finally, the extrusion and characterization of the newly formed 3-methyl-6-phenyl-2,2′-bipyridine. The reaction has been therefore extended to a well-known classical cyclometalating ligand, 2-phenylpyridine, demonstrating that the method is not restricted to rollover derivatives. Following the same step-by-step procedure, 2-phenylpyridine was converted to 2-o-tolyl-pyridine, displaying the potential application of the method to the larger family of classical cyclometalated complexes. The application of this protocol may be useful to convert an array of heterocyclic compounds to their methyl- or alkyl-substituted analogs.